Visual Imprinting in Birds: Behavior, Models, and Neural Mechanisms - McCabe, Brian J. (Frontiers in Physiology, 2019)
Filial imprinting is a process, readily observed in precocial birds, whereby a social attachment is established between a young animal and an object that is typically (although not necessarily) a parent. During a peri-natal sensitive period, the young animal learns characteristics of the object (the imprinting stimulus) simply by being exposed to it and will subsequently recognize and selectively approach this stimulus. Imprinting can thus establish a filial bond with an individual adult: a form of social cohesion that may be crucial for survival. Behavioural predispositions can act together with the learning process of imprinting in the formation, maintenance and modification of the filial bond. Memory of the imprinting stimulus, as well as being necessary for social recognition, is also used adaptively in perceptual classification of sensory signals. Abstract features of an imprinting stimulus, such as similarity or difference between stimulus components, can also be recognized. Studies of domestic chicks have elucidated the neural basis of much of the above behaviour. This article discusses (i) principal behavioural characteristics of filial imprinting and related predispositions, (ii) theoretical models that have been developed to account for this behaviour, and (iii) physiological results elucidating the underlying neural mechanisms. Interactions between these different levels of analysis have resulted in advancement of all of them. Taken together, the different approaches have helped define strategies for investigating mechanisms of learning, memory and perception.